Autoimmune alternating hyper- and hypo-thyroidism: a rare condition in pediatrics. (1st February 2016) - Martins, Luísa Correia; Coutinho, Ana Rita; Jerónimo, Mónica; Caetano, Joana Serra; Cardoso, Rita; Dinis, Isabel; Mirante, Alice
Summary: Alternating between hyper- and hypo-thyroidism may be explained by the simultaneous presence of both types of TSH receptor autoantibodies (TRAbs) – thyroid stimulating autoantibodies (TSAbs) and TSH blocking autoantibodies (TBAbs). It is a very rare condition, particulary in the pediatric age. The clinical state of these patients is determined by the balance between TSAbs and TBAbs and can change over time. Many mechanisms may be involved in fluctuating thyroid function: hormonal supplementation, antithyroid drugs and levels of TSAbs and TBAbs. Frequent dose adjustments are needed in order to achieve euthyroidism. A definitive therapy may be necessary to avoid switches in thyroid function and frequent need of therapeutic changes. We describe an immune-mediated case of oscillating thyroid function in a 13-year-old adolescent. After a short period of levothyroxine treatment, the patient switched to a hyperthyroid state that was only controlled by adding an antithyroid drug. Learning points: Autoimmune alternating hypo- and hyper-thyroidism is a highly uncommon condition in the pediatric age. It may be due to the simultaneous presence of both TSAbs and TBAbs, whose activity may be estimated in vitro through bioassays. The clinical state of these patients is determined by the balance between TSAbs and TBAbs and can change over time. The management of this condition is challenging, and three therapeutic options could be considered: I-131 ablation, thyroidectomy or pharmacological treatment (single or double therapy). Therapeutic decisions should be taken according to clinical manifestations and thyroid function tests, independent of the bioassays results. A definitive treatment might be considered due to the frequent switches in thyroid function and the need for close monitoring of pharmacological treatment. A definitive treatment might be considered due to the frequent switches in thyroid function and the need for close monitoring of pharmacological treatment.